Comparison of Multinational Medical School Students Experiences in the Face of the COVID-19 Pandemic: A Qualitative Analysis - Alexandra C Skockzek; Patrick Ruane; Cassidy Onley; Torhiana Haydel; Maria Ortega; H Dean Sutphin; Alexis Stoner (University Library System, University of Pittsburgh, 2022)
Background:  In the midst of the COVID-19 pandemic, countries, and governments around the world have implemented different measures and guidelines for the containment and mitigation of the COVID-19 virus. In addition to implemented policies and initiatives, social media and personal beliefs have affected medical students' social, emotional, financial, and academic stability and success both domestically and internationally.  Methods:  This qualitative study, recruited students enrolled in the Global Seminar for Health and Environment elective course in their respective medical schools to complete a weekly, non-graded journaling assignment for 6 weeks. To measure outcomes, open-ended questions within the assignment asked students across four different countries (United States, El Salvador, Dominican Republic, and Honduras) questions regarding the COVID-19 pandemic including personal beliefs and knowledge, policies and initiatives within their country, global policies and initiatives, and social media presentations. Thematic analysis was then completed using the QCoder package in R Studio.  Results:  A total of 142 assignment submissions were collected and analyzed. International medical students reported more restrictions in their country, a larger mental health impact, and more individuals in their country showing a lack of regard for policies and initiatives.  United States medical students were more likely to express a decrease in academic opportunities and academic performance. Conclusion:  The COVID-19 pandemic continues to affect medical students globally. The pandemic has changed the medical school experience for both international and United States medical students and affected them not only academically but mentally, and socially.